Perspective on the Primary Prevention of COVID-19: COVID-19 desde la perspectiva de la prevención primaria - Sedano-Chiroque, Franshesca L. (2020)
This article seeks to describe the main primary prevention measures on the 2019-nCoV or COVID-19 that is recently affecting our country, considering epidemiological aspects and recommendations applied and reported in other countries. The topics covered are the prevention of traveling patients, the importance of hand hygiene, respiratory prevention, policies in educational centers and prevention for health personnel. This is due to the need for a better characterization of this new health problem in our country, to establish public policies based on the prevention of complications from this new virus, taking into account assessments based on scientific, preventive and social evidence.